2016
DOI: 10.1016/j.bbacli.2016.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of glutathione levels in the brain tissue samples from HIV-1-positive individuals and subject with Alzheimer's disease and its implication in the pathophysiology of the disease process

Abstract: HIV-1 positive individuals are at high risk for susceptibility to both pulmonary tuberculosis (TB) and extra-pulmonary TB, including TB meningitis (TBM) which is an extreme form of TB. The goals of this study are to determine the mechanisms responsible for compromised levels of glutathione (GSH) in the brain tissue samples derived from HIV-1-infected individuals and individuals with Alzheimer's disease (AD), investigate the possible underlying mechanisms responsible for GSH deficiency in these pathological con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 34 publications
2
28
0
1
Order By: Relevance
“…Antioxidant treatment for HIV was proposed more than two decades ago when it was discovered that plasma levels of cysteine and the cysteine dimer cystine, both precursors for intracellular GSH, as well as GSH itself, are depleted in HIV (121). Consistent with this early work, a recent postmortem study reported low frontal cortex GSH levels in HIV+ subjects (122). As oxidative stress increases and antioxidants can suppress HIV virus replication (123126), antioxidants not only might reduce depression-like behavior but also could help maintain HIV latency.…”
Section: Discussionsupporting
confidence: 79%
“…Antioxidant treatment for HIV was proposed more than two decades ago when it was discovered that plasma levels of cysteine and the cysteine dimer cystine, both precursors for intracellular GSH, as well as GSH itself, are depleted in HIV (121). Consistent with this early work, a recent postmortem study reported low frontal cortex GSH levels in HIV+ subjects (122). As oxidative stress increases and antioxidants can suppress HIV virus replication (123126), antioxidants not only might reduce depression-like behavior but also could help maintain HIV latency.…”
Section: Discussionsupporting
confidence: 79%
“…En addition la carence d'autres antioxydants chez les patients infectés, a été détectée, comme la vitamine A (Chiu et al, 2008) et la vitamine E (Mehta et al, 2010;Pacht et al, 1997). A signaler que l'expression de certains enzymes antioxydants a été réprimée, citant par exemple le GSTP1 (Strange et al, 2001) et ainsi que le -GCS (Morris et al, 2014;Saing et al, 2016).…”
Section: Vih Et Le Stress Oxydantunclassified
“…GSH, a tripeptide comprised of glutamate, cysteine and glycine, functions to protect the cells and tissues from oxidative damage thereby restoring redox homeostasis within the body [20]. Further studies have demonstrated that the biological antioxidant GSH has both antimycobacterial effects and immune-modulating properties [21-23].…”
Section: Introductionmentioning
confidence: 99%
“…Our laboratory has previously reported that the levels of GSH were significantly decreased in the red blood cells, NK cells, macrophages and T cells derived from the peripheral blood of individuals with HIV infection [24-26]. Furthermore, we have also demonstrated that the levels of GSH were significantly compromised in brain tissue samples derived from the frontal cortex of individuals with HIV infection [21]. The decreased levels of GSH among the HIV infected individuals correlated with the diminished control of M. tb infection [21-23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation